2015
DOI: 10.1007/s00427-015-0514-3
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Shep and C. elegans SUP-26 are RNA-binding proteins that play diverse roles in nervous system development

Abstract: The Caenorhabditis elegans gene sup-26 encodes a well-conserved RNA-recognition motif-containing RNA-binding protein (RBP) that functions in dendrite morphogenesis of the PVD sensory neuron. The Drosophila ortholog of sup-26, alan shepard (shep), is expressed throughout the nervous system and has been shown to regulate neuronal remodeling during metamorphosis. Here, we extend these studies to show that sup-26 and shep are required for the development of diverse cell types within the nematode and fly nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Additionally, disruption of either shep or cut function is associated with shortened dendritic branches and field coverage defects. Moreover, cut and shep mutant phenotypes are also highly variable and not fully penetrant, similar to those observed for various caper CC01391 mutant neuronal phenotypes (Schachtner et al, ; Grueber et al, ). In addition to these regulators of branch length, caper CC01391 mutant embryos show aberrant alternative isoform regulation for the gene fry .…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, disruption of either shep or cut function is associated with shortened dendritic branches and field coverage defects. Moreover, cut and shep mutant phenotypes are also highly variable and not fully penetrant, similar to those observed for various caper CC01391 mutant neuronal phenotypes (Schachtner et al, ; Grueber et al, ). In addition to these regulators of branch length, caper CC01391 mutant embryos show aberrant alternative isoform regulation for the gene fry .…”
Section: Discussionsupporting
confidence: 73%
“…The alan shepard ( shep ) gene is widely and primarily expressed in the nervous system and has been shown to regulate metamorphic neuronal outgrowth and development (Chen et al 2014; Schachtner et al 2015). Loss of shep leads to defective outgrowth of peptidergic bursicon neurons, developmental lethality, and behavioral defects, all of which are largely adult-specific (Chen et al 2014).…”
mentioning
confidence: 99%
“…Loss of shep leads to defective outgrowth of peptidergic bursicon neurons, developmental lethality, and behavioral defects, all of which are largely adult-specific (Chen et al 2014). Loss of shep also interferes with the development of nociceptive and proprioceptive neurons in the larval peripheral nervous system (Schachtner et al 2015). In addition, the shep gene has been identified in a number of screens for factors involved in gravitaxis (Armstrong et al 2006), regulation of fat storage (Reis et al 2010), starvation resistance (Harbison et al 2004), cell size determination (Bjorklund et al 2006), and mRNA alternative splicing (Brooks et al 2015).…”
mentioning
confidence: 99%
“…A screen for RBPs and translation factors that are specifically required for dendrite development within Class IV da neurons uncovered 88 candidate genes that regulate dendrite morphology in Class IV da neurons [ 92 ]. Subsequent studies have confirmed that a number of these candidate genes, including brat, shep, caper, 4EHP, oskar and rumpelstiltskin, indeed function in da neuron morphogenesis, and that 12 of these RBPs play a conserved role in dendrite development in C. elegans [ 88 , 93 , 94 , 95 ]. The fact that almost all of these candidates are conserved across metazoa suggests that RNA regulatory mechanisms are critical to the development and function of the nervous system.…”
Section: Additional Roles For Rbps Throughout Drosophilamentioning
confidence: 99%